Extraction and Application of Sesbania Seed Gum (SSG) in CoagulationFlocculation Process - Chua, Siong Chin (Universiti Teknologi PETRONAS, 2018)
The demand of the water increases dramatically throughout the years caused catastrophic water shortage issue in most of the countries. Water treatment has been introduced with the aim to recover the polluted water for domestic usage purpose. Among various water treatment processes, coagulation and flocculation process is widely used as primary treatment due to its simplicity and effectiveness. However, the inorganic coagulants especially aluminium sulfate (alum) that used in coagulation and flocculation process have raised health and environmental issues due to their toxicity. This project aims to produce an effective plant-based coagulant aid by using sesbania seed combine with the use of ferric chloride to replace the existing conventional inorganic coagulant, alum. This project will focus on three main aspects to produce an effective plant-based coagulant aid, sesbania seed gum (SSG) by using sesbania seed.